Online Training Evaluation in Character Building of Training Participants - Yahman Yahman (Jurnal Prajaiswara, 2020)
Training is a short education that combines theory and practice in order to obtain applicable and practical knowledge and skills to improve performance and shape one's character in accordance with organizational demands. Along with the era of industry revolution 4.0 or popularly known as the fourth industrial revolution marked by three key technologies: Internet of things (IoT), BigData, and Artificial Intelligence (AI), online training with utilizing information technology (IT) as a new model in the implementation of training, not least in training for state civil servants (ASN). This research is an evaluation research aimed to find out how far the effectiveness of online training, especially training for state civil servants (ASN) in forming the character of trainees. The method used in this research is a qualitative research method with the selection of respondent samples by purposive sampling. Selected respondents are those who have attended online training in high-level tiered scholarship training, online training for supporting administrative leadership training (PKA) and supervisory leadership training (PKP), and online training participants for PKA and PKP organizers. Data collection is done through interviews and observations. The evaluation model used in Kirk Patrick's training evaluation model consists of four levels, namely reaction, learning, behavior, and result. Of the four stages, three stages are taken, namely reaction, learning, and behavior. Whereas the resulting level is recommended for further research. The results of this study indicate that time and cost are more efficient, but in character, formation is less than optimal.